Editorial Vol11 no1 - Irene Stevens (Scottish Journal of Residential Child Care)
As this issue of the Journal goes to press, the work of the Scottish Institute for Residential Child Care (SIRCC) has been incorporated within a new Centre for excellence for looked after children in Scotland (CELCIS). The new Centre will continue to support the residential child care sector but its remit covers all looked after children, including those in foster care, kinship care and looked after at home. The new Centre aspires to support practitioners, parents and carers to provide the best possible outcomes for children and young people who are looked after at home and away from home and those who have left care. The Scottish Journal of Residential Child Care has played an important function in reporting on research and practice developments and providing a forum for articulating ideas and debate about residential child care, in Scotland and beyond. The Journal will continue to provide an important service to the residential child care community. We are committed to seeking articles which emphasise good practice in residential care. So please continue to send papers for publication.